2019
DOI: 10.1007/s00181-019-01712-6
|View full text |Cite
|
Sign up to set email alerts
|

Employment effect of innovation

Abstract: This publication is a Technical report by the Joint Research Centre (JRC), the European Commission's science and knowledge service. It aims to provide evidence-based scientific support to the European policymaking process. The scientific output expressed does not imply a policy position of the European Commission. Neither the European Commission nor any person acting on behalf of the Commission is responsible for the use that might be made of this publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
1
9
1
Order By: Relevance
“…The process innovation can reduce employment as a direct effect when production technology is improved. However, the process innovation can increase employment as an indirect effect when the demand for lower priced products is higher (Kancs & Siliverstovs, 2017).…”
Section: The Relationship Between Innovation and Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The process innovation can reduce employment as a direct effect when production technology is improved. However, the process innovation can increase employment as an indirect effect when the demand for lower priced products is higher (Kancs & Siliverstovs, 2017).…”
Section: The Relationship Between Innovation and Employmentmentioning
confidence: 99%
“…Similarly, the test results show that technological innovations have no effect on unemployment. Kancs and Siliverstovs (2017) investigated the relationship between R&D expenses and firm's employment through Generalised Propensity Score (GPS) model for 483 firms which are hightech industry in 2007. The results showed that R&D expenses had a positive and significant effect on employment during medium and med-high innovation degree.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is well known that firm's innovation outcomes (product or process) result from a complex process affected by institutional, macroeconomic and technological factors that are usually exogenous of the firm's behavior. Moreover, the mechanisms operating between innovation outcomes and employment described above strongly depend on demand features, market structure and competition (Breemersch et al 2019;Kancs and Siliverstovs 2019). In this regard, recognized the limitations associated with the firm level analysis to capture the displacement and compensation effects (Barbieri et al 2019), we pose that innovation strategies determine innovation outcomes and ultimately affect innovation effects in the firm's workforce quantity and quality.…”
Section: Innovation Strategies and Types Of Innovationmentioning
confidence: 99%
“…However, the relationship between technical change and employment is a classic topic that has received attention from diverse research streams, based on different theoretical basis and at different aggregation levels (Dosi and Mohnen 2019;Calvino and Virgillito, 2018;Vivarelli 2014;Freeman et al 1992). This wide and large body of literature has demonstrated that there is a complex, no linear relationship between innovation and employment which effects are neither homogenous nor immediate (Herstad and Sandven 2019;Kancs and Siliverstovs 2019;Piva and Vivarelli 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the only paper that examines the non-linear unemployment-innovation nexus is Kancs and Siliverstovs (2019). They empirically test the assumption of a non-linear relationship between employment and innovation intensity (research and development expenditure to sales) and examine the assumptions using firm-level data.…”
Section: Introductionmentioning
confidence: 99%